2006
DOI: 10.3892/ijmm.18.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Regucalcin increases Ca2+-ATPase activity in the heart mitochondria of normal and regucalcin transgenic rats

Abstract: Abstract. The role of regucalcin, a regulatory protein in intracellular signaling system, in the regulation of Ca 2+ -ATPase activity in rat heart mitochondria was investigated. Mitochondrial Ca 2+ -ATPase activity was significantly increased by increasing concentrations of CaCl 2 (2.5-50 μM). An increase in the enzyme activity was saturated at 50 μM CaCl 2 . The addition of regucalcin (10 -11 -10 -8 M) in the enzyme reaction mixture caused a significant increase in Ca 2+ -ATPase activity in heart mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The mitochondrial Ca 2+ -ATPase activity was increased with increasing concentrations of CaCl 2 (2.5–50 μM) (21). An increase in the enzyme activity was saturated at 50 μM CaCl 2 .…”
Section: Regucalcin Regulates Intracellular Ca2+ Homeostasis In Thmentioning
confidence: 99%
See 3 more Smart Citations
“…The mitochondrial Ca 2+ -ATPase activity was increased with increasing concentrations of CaCl 2 (2.5–50 μM) (21). An increase in the enzyme activity was saturated at 50 μM CaCl 2 .…”
Section: Regucalcin Regulates Intracellular Ca2+ Homeostasis In Thmentioning
confidence: 99%
“…The role of regucalcin in the regulation of Ca 2+ -ATPase activity in rat heart mitochondria was also demonstrated ( 21 ). The mitochondrial Ca 2+ -ATPase activity was increased with increasing concentrations of CaCl 2 (2.5–50 μM) ( 21 ). An increase in the enzyme activity was saturated at 50 μM CaCl 2 .…”
Section: Regucalcin Regulates Intracellular Ca 2+ mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that regucalcin can activate Ca 2+ -ATPase, which has a role as a Ca 2+ pump, in rat heart microsomes (12) and mitochondria (20), indicating that regucalcin plays a role in the regulation of Ca 2+ homeostasis in heart cells. Moreover, regucalcin has been demonstrated to regulate the activities of nitric oxide synthase (21), protein phosphatase (22), and superoxide dismutase (23), which is related to intracellular signaling, in rat heart cytosol.…”
Section: Introductionmentioning
confidence: 99%